Preparation and Performance Research of Concrete Appearance Beautification Material - TANG Shi, ZHANG Peng-fei, ZHANG Jin-hao, CHEN Yu-chen (Cailiao Baohu, 2021)
For improving the concrete structure appearance and service durability, a kind of concrete appearance beautification and anti-corrosion material was developed. This material included three layers of bottom, middle and surface, which played different roles and co-constituted a system of beautification and anti-corrosion materials. In addition, A hydrophobic layer was formed between the bottom layer and the surface of the substrate, the middle layer solved the problem of concrete color difference, and the surface layer protected the structure appearance and increased the durability through isolating the outside. Compared with other coatings system, the results of performance comparison showed that the concrete appearance beautification and anti-corrosion material had excellent breathable, waterproof properties, which could effectively improve the durability of the concrete structure.